Yinglish in Woody Allen’s films: A dubbing issue - Brisset, Frédérique (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2013)
A prominent representative of the Jewish-American population, Woody Allen often refers to his Ashkenazi origins in his films in a self-derisive way. His dialogues are interspersed with Yinglish, a feature which offers a serious challenge to French translators, especially for the dubbed versions of the films. Dubbing remains the prevalent mode of audiovisual translation in France and provides many opportunities to manipulate and alter the original film soundtrack. This article presents a comparative analysis of examples from Allen's dialogues and the French dubbed versions, in an attempt to unearth the strategies used by translators in view of adapting to the diverging abilities of the target audience. Two semantic fields are under scrutiny: the religious Jewish technolect and Yiddish slang, a humorous device which serves the needs of protagonist characterization and is widely assimilated by American English. The examples are taken from eight comedies by Allen, covering a thirty-four-year time span in the director's extensive career.